Elaboração e validação do conteúdo de um algoritmo para o planejamento da administração de medicamentos intravenosos em neonatos - Anna Caroline Leite Costa (2022)
Introduction: Intravenous therapy (IVT) is an activity comprising prescribing, dispensing, preparing, administering and monitoring the use of medications, requiring fast and accurate decision-making and safe and effective techniques. However, this procedure has associated risks, especially in newborns, due to factors such as their physiological specificities and inability to communicate verbally. It is therefore necessary to invest in strategies to promote the safety of neonates, such as algorithms, which stand out for organizing, systematizing and standardizing actions, contributing to safe decision-making, reducing incidents associated with IVT and promoting quality and safety of care. However, no algorithms were found to guide nurses in planning and systematizing the administration of IVT in neonates, highlighting the need to build and validate an algorithm for this purpose. Objective: To create and to validate the content and appearance of an algorithm for planning and systematizing the process of intravenous drug administration in neonates. Method: This is a methodological study of content and appearance validation. A scope review was carried out in order to support the construction of the algorithm. Thirty-five experts were invited to validate the instrument, and they were selected through a search on the Lattes Platform and by the “snowball” technique. 14 judges agreed to participate in the study. The data characterizing the professionals were analyzed according to descriptive statistics using the Statistical Package for Social Sciences version 19.0. The experts' opinion regarding the items of the algorithms was evaluated according to the Content Validity Index (CVI), with items with CVI ≥ 0.8 being considered acceptable. The experts agreed to participate by accepting the Free and Informed Consent Term. Results: 31 references were included in the scope review, extracting categories for the analysis, which were named: indications for intravenous access; care related to polypharmacy; care prior to the administration of intravenous medications; care related to catheter handling; and care related to drug infusion. These categories guided the construction of the algorithm, which was validated after three rounds, in which 14 experts participated in the first two and, in the last, 13. The average age of the participants was 42.8 years (SD ± 8.0), while the average time since graduation was 19.3 years (SD ± 8.5) and the time working in neonatology and/or pediatrics was 17.6 years (SD ± 9.7). As for current professional occupation, most respondents have more than one job, with 84.6% in the area of education (n= 11), research 69.2% (n= 9) and assistance 46.1% (n= 6). Regarding the algorithm items, 17 were validated in the first round, 18 in the second round, four in the third and only one item was excluded during the process. Conclusion: The content and appearance of an algorithm was built and validated to guide nurses in decision-making regarding the administration of medication in neonates, contributing to qualified and safe care. There is a need to invest in studies to confirm their clinical validation and effectiveness.